Case Report: Differential lung ventilation with jet ventilation via a bronchial blocker for a patient with a large thoracogastric airway fistula after esophagectomy - Wu, Wenqi; Li, Sibei; Song, Xiuling; Wang, Xia; Wang, Yong; Cai, Chengyi; Wang, Jiyong; Li, Yuhui; Ma, Wuhua (Frontiers in Surgery, 2022)
Background A thoracogastric airway fistula (TGAF) is a rare and potentially fatal complication of esophagectomy for esophageal and cardia carcinomas. Isolation of the fistula and pulmonary separation is necessary during the surgical repair of a tracheal fistula. However, currently, the reported airway management techniques are not suitable for patients with a large TGAF. This case study presents an alternative technique for performing differential lung ventilation in a patient with a thoracogastric airway fistula. Case presentation A 70-year-old man was diagnosed with a thoracogastric airway fistula situated above the carina after esophagectomy, and a thoracoscope-assisted repair of the fistula and pectoralis major myocutaneous flap transplantation were scheduled. The patient could not tolerate one-lung ventilation and the complex intubating operation due to aspiration pneumonia and the size (3.5 cm × 1.7 cm) of the fistula. We, therefore, performed differential lung ventilation in which an extended 6.5#single-lumen endotracheal tube was inserted into the left main bronchus and a 9Fr bronchial blocker was placed in the right main bronchus by using the video-flexible intubation scope. The right lung was selectively inflated with jet ventilation, while positive pressure ventilation was maintained through the left endotracheal tube. The value of SPO2 remained above 95% throughout the operation. Conclusion For patients with a large thoracogastric airway fistula, differential lung ventilation of a combination of positive pressure ventilation and jet ventilation is useful. Inserting an extended single-lumen endotracheal tube into the left main bronchus and a bronchial blocker into the right main bronchus could be another way of providing differential ventilation for patients with a large thoracogastric airway fistula.